Preparing pets and their people: opportunity for veterinary teams to promote disaster preparedness in their communities - Quintana, Joedy; Viola, Lindsey; Sanchez, Valeria; Scott, Danielle; Duncan, Colleen (Frontiers in Veterinary Science, 2025)
Climate change has made disasters, and their associated health risks, more frequent and severe. Despite these growing risks, a substantial proportion of adults in the US do not have a disaster plan. Even for those who have disaster plans, it is unclear if these always include pets. The objective of this project was to explore the potential for veterinary teams to facilitate the development of pet-inclusive disaster plans through conversations during routine veterinary visits. We conducted two separate anonymous surveys, one for veterinary staff and one for veterinary clients. Overall, we found that both groups believe disasters are increasing and likely to impact people and their pets, however respondents remain largely unprepared for these events. Although both groups reported that the topic of disaster preparedness was not typically covered during veterinary visits, pet owners overwhelmingly agreed that pet health professionals are trustworthy sources of information, and that it would be helpful to have support from their veterinary team in developing a disaster plan that includes their pets. Barriers to such conversations, and potential solutions, were explored. Collectively these findings reinforce the role of veterinary professionals as trusted community members who can enhance public health and community resilience by integrating disaster preparedness into their practice.